Exploring the potential of smartphone applications as educational tools in the Ecology teaching–learning process - Lucimara Lessa dos Santos; Maria Lenilda Caetano França; David Gadelha da Costa; Guilherme Ramos Demetrio (Discover Education)
Abstract The integration of digital technology into education offers new avenues to enhance Ecology education by addressing resource limitations and fostering student engagement. This study examines the potential of smartphone applications as didactic tools for teaching Ecology in Brazilian basic education. Through a targeted search on the Google Play Store, we identified 290 apps, of which only 29 met the criteria for Ecology-focused education. These apps were categorized by type (e.g., games, e-books) and evaluated for pedagogical value, technical quality, and interactivity using an established assessment protocol. The analysis revealed a limited number of high-quality apps, with scores ranging from 39 to 88 (mean = 67.36, SD = 12.23). Most apps were reference materials, followed by games and e-books. A word cloud analysis revealed that “biomes” was the most frequently addressed theme, followed by topics like Brazilian ecosystems, recycling, and ecological interactions, aligning with the Brazilian National Common Curricular Base. No significant correlations were found between app type, download volume, and quality, suggesting that app quality does not necessarily correlate with popularity. Our findings highlight the need for more diverse, high-quality applications to support Ecology education, emphasizing the potential of digital tools to assist teachers and enhance student learning.